Improvement of beam transport and target station of technological linac “EPOS” - Dronov, R.N.; Reprintsev, L.V.; Tatanov, V.I. (Вопросы атомной науки и техники, 2020)
To increase the reliability of operation and simplify the precise tuning of the beam it is proposed to upgrade the output part of the accelerator “EPOS” NSC KIPT that operates in the range of electron energies 25…35 MeV and beam power up to 12 kW. An additional collimator, beam profile scanner and a wide aperture beam current monitor is offered to install. It is also proposed to upgrade the target station, which will improve the quality of irradiation and improve working conditions for personnel.